1981
DOI: 10.1007/bf00253821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on glucagon secretion mediated via glucose metabolism of pancreatic a cells in ducks

Abstract: A possible action of insulin via glucose metabolism on the pancreatic A cell response to glucose, was studied in ducks. 2-Deoxyglucose, a nonmetabolizable analogue of glucose was used. In normal ducks, the hyperglycaemia induced by 2-deoxyglucose (IV: 0.5 g/kg) resulted in hyperglucagonaemia, while the same degree of hyperglycaemia, induced by glucose infusion (IV injection 25 mg/kg, and infusion 5 mg/kg/min) immediately suppressed glucagon secretion. In diabetic ducks, two days after subtotal pancreatectomy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
1
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
1
1
2
Order By: Relevance
“…None of the hexoses nor their derivatives were found to stimulate glucagon secretion. While several investigations have reported that 2-DG stimulated glucagon secretion in vivo (Muller, Faloona and linger 1971;Hedo, Villanueva and Marco 1978;Werner, Benson, Brodsky, Hollander, Asplin, Johnson and Palmer 1980;Laurent, Gross, Lakili and Mialhe 1981) or in vitro {Weir, Knowlton and Martin 1974;Hahn and Ziegler 1977;Gerich, Langlois, Noacco, Karam and Forsham 1973), 2-DG inhibited glucagon secretion markedly and significantly in our studies.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…None of the hexoses nor their derivatives were found to stimulate glucagon secretion. While several investigations have reported that 2-DG stimulated glucagon secretion in vivo (Muller, Faloona and linger 1971;Hedo, Villanueva and Marco 1978;Werner, Benson, Brodsky, Hollander, Asplin, Johnson and Palmer 1980;Laurent, Gross, Lakili and Mialhe 1981) or in vitro {Weir, Knowlton and Martin 1974;Hahn and Ziegler 1977;Gerich, Langlois, Noacco, Karam and Forsham 1973), 2-DG inhibited glucagon secretion markedly and significantly in our studies.…”
Section: Discussioncontrasting
confidence: 59%
“…Insulin secretion was not observed during any perfusion except that involving 16.7mM glucose and 20 mM glucosamine. It has been reported that glucagon secretion from A cells is regulated by insulin from B cells (Samols, Tyler and Marks 1972;linger et al 1977;Laurent et al 1981;Filipponi, Gregorio, Cristallini, Ferrandina, Nicoletti and Santeusanio 1986). From the present data, inhibition of IRG secretion might result from a direct action of the hexoses on the A-cells.…”
Section: Discussionsupporting
confidence: 56%
“…En las aves, los islotes se describen de acuerdo con la especie y el sitio lobar; sin embargo, de manera general los islotes están formados por cuatro tipo de células distintas: α, β, δ y F, productoras respectivamente de glucagón, insulina, somatostatina y polipéptido pancreático (2)(3)(4)(5). La insulina es una hormona anabólica que regula el metabolismo de glucosa, lípidos, proteínas y factor de crecimiento (6).…”
Section: Introductionunclassified
“…La liberación de insulina en las aves no se afecta por el ayuno, las hormonas y la estimulación vagal. En sistemas aviar in vitro, la insulina no tiene efectos antilipolíticos y es poco lipogénica; esta es una diferencia en relación con los mamíferos y humanos (4,9). Los receptores β-adrenérgicos en pollos regulan la secreción adrenérgica de insulina (21).…”
Section: Introductionunclassified
“…Most of our knowledge of the avian endocrine pancreas originates from experimental work with domestic granivorous species, chiefly Anseriformes (Laurent et al, 1981;Karmann & Mialhe, 1982). Some studies indicate that these species may differ from mammals in the physiology of blood glucose control.…”
Section: Introductionmentioning
confidence: 99%